INTRANS: AN EMERGING DESIGN OF MALAYSIAN NATIONAL IDENTITY IN TRANSFORMING SCULPTURE - Azwan Abdul Karim; Nik Zulkarnaen Khidzir; Zukeri Ibrahim; Abdul Aziz Zalay @ Zali, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The first transforming sculpture was introduced in Japan by Tomoo Yamaji in the year 2000, and he became one of the artists who popularized this style. Since then, many artists have attempted to replicate this transforming style; however, they have not reached the same standard or style as Yamaji’s sculptures. Additionally, there are very few adaptations of this style or concept worldwide, especially in Malaysia. Therefore, we aim to adapt this concept from Malaysia’s perspective, incorporating both 2-dimensional and 3-dimensional design elements through the Interactive Transforming Sculpture (INTRANS) branding to showcase national identity on a global scale. To realize this innovative INTRANS concept, we need to investigate the appropriate processes and requirements. This involves examining materials and techniques through observation and analysis of previous artworks by various artists, which could help design a sculpture that embodies Malaysian national identity and assist Malaysian sculptors in embracing this identity. Literature indicates that there is a very limited number of fine artists interested in applying this kind of sculpture technique, primarily due to a lack of knowledge about transforming mechanisms and a lack of passion. The adaptation of this concept could lead to further research and development in INTRANS creative innovation.